Leaf photosynthesis and yield components of mung bean under fully open-air elevated [CO2] - Ji GAO; Xue HAN; Saman Seneweera; Ping LI; Yu-zheng ZONG; Qi DONG; Er-da LIN; Xing-yu HAO (Journal of Integrative Agriculture, 2015)
Mung bean (Vigna radiata L.) has the potential to establish symbiosis with rhizobia, and symbiotic association of soil micro flora may facilitate the photosynthesis and plant growth response to elevated [CO2]. Mung bean was grown at either ambient CO2 400 µmol mol−1 or [CO2] ((550±17) µmol mol−1) under free air carbon dioxide enrichment (FACE) experimental facility in North China. Elevated [CO2] increased net photosynthetic rate (Pn), water use efficiency (WUE) and the non-photochemical quenching (NPQ) of upper most fully-expanded leaves, but decreased stomatal conductance (Gs), intrinsic efficiency of PSII (Fv′/Fm′), quantum yield of PSII (ϕPSII) and proportion of open PSII reaction centers (qP). At elevated [CO2], the decrease of Fv′/Fm′, ϕPSII, qp at the bloom stage were smaller than that at the pod stage. On the other hand, Pn was increased at elevated [CO2] by 18.7 and 7.4% at full bloom (R2) and pod maturity stages (R4), respectively. From these findings, we concluded that as a legume despite greater nutrient supply to the carbon assimilation at elevated [CO2], photosynthetic capacity of mung bean was still suppressed under elevated [CO2] particularly at pod maturity stage but plant biomass and yield was increased by 11.6 and 14.2%, respectively. Further, these findings suggest that even under higher nutrient acquisition systems such as legumes, nutrient assimilation does not match carbon assimilation under elevated [CO2] and leads photosynthesis down-regulation to elevated [CO2].